Knowledge and use of emergency contraceptives among women seeking termination of pregnancy in JB Marks subdistrict, North West Province - Van Nieker, Elsje (My University, 2024)
Background: Despite acceptable contraceptive coverage rates in South Africa the rise in the number of termination of pregnancies are worrisome and suggest that family planning services are not yet optimal. Emergency contraceptives are underutilized in South Africa and poor knowledge regarding emergency contraceptives may be a contributing factor. Objectives: To assess the knowledge and use of emergency contraceptives among women presenting to a termination of pregnancy (TOP) facility in the JB Marks sub-district, North West Province, South Africa. Methods: This cross-sectional study was based at the TOP clinic at Potchefstroom Hospital, North West Province, South Africa. One-hundred-and-ninety-six women completed selfadministered questionnaires during November 2020 to July 2021. Results: The mean age of the women was 26.5 years (range 18-45 years). Most participants were single (58.2%). More than half of the women (55%) had a poor knowledge of emergency contraceptives. This could contribute to the poor uptake (17.4%) of emergency contraceptives. There was no statistical significance between residence, education and knowledge with the uptake of emergency contraceptives. Conclusion This study highlighted that knowledge and usage of emergency contraception is low in women presenting for TOP in the JB Marks sub-district. Emergency contraceptives can reduce the amount of unintended pregnancies and its associated trauma significantly. Community intervention should be of utmost importance to improve not only the knowledge and usage of emergency contraception.
A research report submitted in partial fulfilment of the requirement for the degree of Master of Medicine (MMed) in Family Medicine to the Faculty of Health Sciences, University of the Witwatersrand, School of Clinical Medicine, Johannesburg, 2023
Keywords: Termination of pregnancy (TOP); Emergency contraceptives; Family planning; SDG-3: Good health and well-being